1990
DOI: 10.1002/chin.199047250
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and in vivo Antitumor and Antiviral Activities of 2′‐Deoxyribofuranosyl and Arabinofuranosyl Nucleosides of Certain Purine‐6‐sulfenamides, ‐sulfinamides and ‐sulfonamides.

Abstract: The amination products (III) from the thiopurines (I) are oxidized to the corresponding (R,S)‐sulfoxides (IV) or sulfones (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the quest for searching for an exclusive application of alternating current protocols in organic synthesis, we discovered that the radical-radical cross-coupling to form an N-S bond represents a suitable class of reaction, that could not be delivered via DC electrolysis (Figure 1E and 1F). N-S bonds are versatile structural components, because they are ubiquitous structural motifs present in many valuable molecules (Figure 2A), [25][26][27][28][29][30][31][32][33] and also valuable reagents in organic transformations. [34][35][36][37][38][39][40] Over the past decades, methods for N-S bonds containing compounds synthesis have been largely developed.…”
Section: (B) Previous Methods For N-s Bonds Formation (C) Our Design For N-s Bonds Formationmentioning
confidence: 99%
“…In the quest for searching for an exclusive application of alternating current protocols in organic synthesis, we discovered that the radical-radical cross-coupling to form an N-S bond represents a suitable class of reaction, that could not be delivered via DC electrolysis (Figure 1E and 1F). N-S bonds are versatile structural components, because they are ubiquitous structural motifs present in many valuable molecules (Figure 2A), [25][26][27][28][29][30][31][32][33] and also valuable reagents in organic transformations. [34][35][36][37][38][39][40] Over the past decades, methods for N-S bonds containing compounds synthesis have been largely developed.…”
Section: (B) Previous Methods For N-s Bonds Formation (C) Our Design For N-s Bonds Formationmentioning
confidence: 99%
“…Revankar et al [69] reported elimination of 2'-deoxy-6-thioinosine and 9-β-Darabinofuranosyl-6-thiopurine with chloramine to prepare corresponding 6sulfenamides which on oxidation by excess metachloroperbenzoic acid (mCPBA) produced corresponding sulfonamide in 48% yield (scheme 19). (mCPBA) was used as an oxidizing agent for the oxidation of sulfur to produce the corresponding sulfone.…”
Section: Scheme 18; Synthesis Of Sulfonamide From Sulfonic Acid Usingmentioning
confidence: 99%